PERKEMBANGAN METAKOGNITIF PESERTA DIDIK KELAS V DI SEKOLAH DASAR KOTA BANDAR LAMPUNG - ., Herpratiwi (LPPM Universitas Hein Namotemo, 2018)
ABSTRAK Pendekatan konstrutivis sudah dilakukan oleh banyak pendidik untuk mencapai tujuan pembelajaran yang berkaitan untuk membangun pengetahuan tingkat tinggi yaitu meta kognitif. Untuk itu perlu dilakukan kajian yang bertujuan untuk mendeskripsikan perkembangan metakognitif  peserta didik kelas V Sekolah Dasar di Kota Bandar Lampung. Penelitian ini merupakan penelitian survai,  untukmengungkap fakta tentang perkembangan metakognitif  peserta didik SD kelas V di Kota Bandar Lampung.  Populasi dalam penelitian ini peserta didik yang memiliki ragking 1, 2 dan 3, dimana jumlah SDN 186 sekolah.  Sampel diambil melalui stratified random sampling, yaitu SD yang terakreditas A dengan jumlah 40 SD.  Besarnya ukuran sampel dengan sampel secara acak/ random proporsional (proporsional sampling).  Data dikumpulkan denganMetacognitive Awareness Inventory (MAI). Pengimplementasian MAI dilakukan pada saat peserta didik berada di semester 1.Perkembangan  metakognitif didasarkan pada kriteria  Schraw & Dennison,yaitu  buruk (≤50), kurang (51-69), cukup (70-79), dan baik (80≤). Kesimpulan penelitian adalah: (a) perkembangan kemampuan metakognitif peserta didik kelas V Sekolah Dasar di Kota Bandar Lampung masih masuk dalam kategori kurang, (b) skor tertinggi perkembangan kemampuan metakognitif peserta didik kelas V Sekolah Dasar pada aspek pengetahuan metakognitif  adalahconditional knowledge, dan yang terendah procedural knowledge.Dan (c) skor tertinggi perkembangan kemampuan metakognitif peserta didik kelas V Sekolah Dasar pada aspek regulasi  metakognitif  adalah planning, dan yang terendah information management. ABSTRACT The constructivist approach has been carried out by many educators to achieve objectives-related learning to buildhigh-level of knowledge, namely metacognitive. Therefore, it is necessary to conduct a study that aims to describe the metacognitive development of fifth grade students of elementary schools in Bandar Lampung. This research was a survey research, to reveal the facts about metacognitive development of fifth grade elementary school students in Bandar Lampung. The population in this study is students who are ranked 1, 2 and 3, in 186 schools. Samples were taken through stratified random sampling and the number of sample are 40 accredited elementary schools. The size of the sample is defined by proportional random sampling. Data was collected by a Metacognitive Awareness Inventory (MAI). The implementation of the MAI was carried out when students are in the first semester. Metacognitive development arebased on the Schraw & Dennison criteria, which are poor (≤50), lack (51-69), adequate (70-79), and good (80≤). The conclusions of the study were: (a) the development of the metacognitive abilities of the fifth grade students of elementary schools in Bandar Lampung was still in the poor category, (b) the highest score of the development of metacognitive abilities of students in the fifth grade of elementary school on the metacognitive knowledge aspectswas conditional knowledgeand the lowest procedural knowledge, and (c) the highest score of the development of the metacognitive abilities of students in the fifth grade of elementary schools in the aspect of metacognitive regulation was planning, and the lowest was information management.